2020
DOI: 10.1155/2020/8760563
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels and Placental Expression of NGAL in Gestational Diabetes Mellitus

Abstract: Objectives. The aim was to investigate neutrophil gelatinase-associated lipocalin (NGAL) levels in the serum and term placentas and its potential role in gestational diabetes mellitus (GDM). Methods. A total of 49 GDM subjects and 39 age-matched women with normal pregnancies were recruited. We examined serum concentrations of NGAL and tumor necrosis factor-α (TNF-α) in maternal blood and cord blood and their expression levels in the term placentas and umbilical cord. Results. Serum NGAL levels were significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
(39 reference statements)
1
13
0
Order By: Relevance
“…[12,39]. By pooling the current evidence, our results were in chord with findings from previous studies mainly conducted in Chinese population [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], showing that circulating NGAL levels were higher in GDM cases compared to healthy controls. For instance, in a cohort study involving 41 women with a singleton pregnancy, who developed GDM in the past 12 months, and healthy group of 82 normal pregnancies, the levels of circulating NGAL were significantly higher in those with GDM than that of control group [51.3 ng/mL (39.8-66.1) vs. 17.8 ng/mL (15.5-20.9); p < 0.001] in the first trimester [13].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…[12,39]. By pooling the current evidence, our results were in chord with findings from previous studies mainly conducted in Chinese population [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], showing that circulating NGAL levels were higher in GDM cases compared to healthy controls. For instance, in a cohort study involving 41 women with a singleton pregnancy, who developed GDM in the past 12 months, and healthy group of 82 normal pregnancies, the levels of circulating NGAL were significantly higher in those with GDM than that of control group [51.3 ng/mL (39.8-66.1) vs. 17.8 ng/mL (15.5-20.9); p < 0.001] in the first trimester [13].…”
Section: Discussionsupporting
confidence: 86%
“…For instance, in a cohort study involving 41 women with a singleton pregnancy, who developed GDM in the past 12 months, and healthy group of 82 normal pregnancies, the levels of circulating NGAL were significantly higher in those with GDM than that of control group [51.3 ng/mL (39.8-66.1) vs. 17.8 ng/mL (15.5-20.9); p < 0.001] in the first trimester [13]. Furthermore, another study including 49 GDM subjects and 39 age-matched women with heathy pregnancies not only reported significantly higher level of serum NGAL in GDM women compared with the control in maternal blood (4.80 ± 1.99 vs. 3.66 ± 1.13, p = 0.001) and cord blood (4.70 ± 2.08 vs. 3.85 ± 1.44, p = 0.027), but also found positive correlation between NGAL levels and different clinical markers of insulin resistance (Pearson's correlation coefficient or Spearman's corre-lation coefficient ranged from 0.253 to 0.624, all p < 0.05) [30]. Consistently, a Chinese study involving 260 pregnant women showed that, plasma NGAL concentrations tended to be statistically higher in women with GDM and normal prepregnancy BMI (group 2) and in those with GDM and overweighted BMI (group 3) compared with healthy pregnant women with normal BMI (group 1) (p < 0.001 for both group comparisons) [22].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The NGAL is a lipocalin superfamily member, which was first discovered and named by Lars Kjeldsen in 1993 (12). Normally, NGAL is released from a small amount of neutrophils in bone marrow while under pathological conditions, and it is also upregulated and released by a variety of other cells, such as activated neutrophils, macrophages, and non-hematopoietic epithelial cells (13,14). Meanwhile NGAL is a novel marker of AKI (15,16), and it has been identified as a highly sensitive and nonspecific predictor of AKI injury in pediatric septic shock (17).…”
Section: Discussionmentioning
confidence: 99%